A legal approach to the national emergency management of space weather: China as a case study. (September 2022) - Yan, Yongliang
Abstract: The attention of the international space community has been drawn to space weather over the last two decades, not only because of its uncertainty and its adverse effects on the safety of space operations and the long-term sustainability of outer space activities (LTSOSA), but also because of its negative societal and economic impacts on the ground. The national emergency management of space weather is indispensable for China because China has both a large number of assets in outer space and infrastructure on the ground that are vulnerable to space weather. While China gives weight to the monitoring of space weather events by deploying a series of space- and ground-based systems, its national-level management of space weather events is inadequate. China, compared to the USA, is still a long way from having scientific and effective emergency management of severe space weather in the areas of space weather science research, response, and rulemaking. Current international hard laws that address the space weather issue play a limited role because these rules are all general. The Guidelines for the Long-term Sustainability of Outer Space Activities of the Committee on the Peaceful Uses of Outer Space (the UNCOPUOS Guidelines for the LTSOSA), although they provide soft-law guidance addressing the harmful impacts of space weather on space activities from the perspectives of mitigation, preparedness, monitoring, and early warning, neither address the response to or recovery from extreme space weather events in outer space nor provide for space weather mitigation, preparedness, response, and recovery regimes on the ground. Apart from the international law and the soft-law guidance, Chinese national laws only provide general guidelines for the emergency management of space weather. To enhance its national capacity to address space weather and minimize the harmful societal and economic impacts of space weather, a comprehensive legal regime for the emergency management of space weather should be in place in China; this should primarily revolve around mitigation, preparedness, monitoring, early warning, response, recovery, capacity-building, and international cooperation. Highlights: The national emergency management of space weather in China is inadequate compared to that in the USA. Comprehensive national emergency management of space weather from a legal perspective is indispensable for China. The space weather regime primarily addresses mitigation, preparedness, monitoring, early warning, response, and recovery.